Experiences of the quality of care of women with near‐miss maternal morbidities in the UK. (September 2014) - Hinton, L; Locock, L; Knight, M
Abstract : We undertook a qualitative interview study of women's and their partners' experiences of severe pregnancy complications. Across the care pathway, women identified a number of examples of good practice that made an important difference to their recovery. There were some areas where women felt the quality of care could be improved, for example during points of transition between higher level and routine care or from hospital to the community. Longer‐term support and counselling were felt to be particularly valuable, and yet not always universally available. These results emphasise the importance of integrated quality care across the whole patient pathway.